Posledice neudeležbe strank na glavni obravnavi v upravnem sporu - Lovšin, Špela (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2021)
The paper discusses legal consequences of non-attendance of the parties at the main hearing in administrative dispute. Their regulation in the Slovene Administrative Dispute Act (ADA) is very limited, which often creates dilemma for administrative judges about how to carry on the proceedings in the event of the parties’ non-attendance. The growing importance of the right to main hearing in administrative dispute further contributes to this dilemma. In the first part, the paper examines the substance of the right to a main hearing in administrative dispute, consequences of non-attendance of the parties in the legal regimes of selected European countries and in the Slovene regulation of civil procedure. The second, central part of the paper analyses the consequences of non-attendance of the parties as provided in the current ADA and in the proposal of its amendment, which fails to address the issue comprehensively. The paper is concluded by the authors’ proposals of de lege ferenda regulation.
Keywords: glavna obravnava (pravo); pravdni postopek; sodišča; sodni postopek; sodniki; Upravni spor